Factor Influencing Technological Innovation Performance (Journal of Engineering and Health Sciences, 2019)
Innovation is not just an individual study by a company or an entrepreneur, but it has to be in a larger system that enables innovation. There is a need, therefore to study the external and internal factors that influence the output of technological innovation. The goal of this study was to identify the factor that influence of the performance in technology innovation defined from several researchers.  The role of innovation as a critical factor influencing a company’s business creativity and competitiveness make it essential to growth of productivity and productivity of the industry. Various studies of innovation is identified as helping companies open new markets and gain competitive advantage succeeded in increasing market share and achieving sustainable competitiveness.